Fracture of modified urethane - methacrylate resins - Zhang, Xiangcheng (Cranfield University, 1993)
Fracture and toughening mechanisms in rubber modified and hybridized urethane-methacrylate resins have been investigated. Fracture mechanisms are defect-dominated in the unmodified resin. The relationships between defect size and fracture strength are characterized through the critical stress intensity factor KIC. Low fracture toughness and high crack sensitivity of the unmodified resin is due to lack of plastic deformation at the crack tip. A 10-fold increase in fracture resistance in the resin has been achieved through rubber modification. The main reason for the improvement is due to occurring of intensive plastic deformation in the presence of rubber, which effectively eases stress concentrations and spreads them away from the crack tip. Deformation mechanisms in rubber-modified resins are shear-dominated. Cavitation of rubber plays a key role in inducing shear deformation in the matrix. Fracture processes in rubber-modified resins start from coalescence and linkage of voids initiated inside rubber particles within rubber domains, which leads to final fracture in the resin matrix. Further increase in KIC was also obtained by incorporation of filler in a matrix toughened with rubber. This increase is not due to the effect of crack front pinning but due to increase in Young’s modulus in the presence of rigid filler. The same deformation and fracture mechanisms operate in the hybrid resins as in the rubber-modified ones.